2018
DOI: 10.1111/1467-8500.12328
|View full text |Cite
|
Sign up to set email alerts
|

Climate change policy discontinuity and its effects on Australia's national electricity market

Abstract: Australia's National Electricity Market (NEM) became unstable in 2016/2017 after 20 years of consistent performance. The South Australian grid collapsed on 28 September 2016 – Australia's first black system event since 1964. Wholesale prices in the region trebled to $120+/MWh; soon after Hazelwood power station announced its exit with just 5 months’ notice. The problem spread as prices elsewhere doubled to $89/MWh from a long‐run average of $42.50. The NEM is experiencing a supply‐side crisis. Consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 46 publications
(197 reference statements)
0
52
0
Order By: Relevance
“…See Parliament of Australia at: http://parlinfo.aph.gov.au/parlInfo/search/display/display.w3p;query%3DId%3A%22chamber%2Fhansardr%2F1997-11-20%2F0016%22accessed August 2017). 1999a, 1999bNelson et al 2010;Simshauser & Tiernan 2018 via a statebased national ETS scheme (see NETT, 2006;Nelson et al 2010;Jones, 2014) and again from 2008-2010 (see Buckman & Diesendorf, 2010;Garnaut, 2014). On the fourth attempt the policy development cycle from 2011-2012 was implemented and a carbon tax transitioning to an ETS was implemented from 2012-2014 only to be killed off following a general election and change of government in 2013 (see Freebairn, 2014;Wild et al 2015).…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations
“…See Parliament of Australia at: http://parlinfo.aph.gov.au/parlInfo/search/display/display.w3p;query%3DId%3A%22chamber%2Fhansardr%2F1997-11-20%2F0016%22accessed August 2017). 1999a, 1999bNelson et al 2010;Simshauser & Tiernan 2018 via a statebased national ETS scheme (see NETT, 2006;Nelson et al 2010;Jones, 2014) and again from 2008-2010 (see Buckman & Diesendorf, 2010;Garnaut, 2014). On the fourth attempt the policy development cycle from 2011-2012 was implemented and a carbon tax transitioning to an ETS was implemented from 2012-2014 only to be killed off following a general election and change of government in 2013 (see Freebairn, 2014;Wild et al 2015).…”
Section: 2mentioning
confidence: 99%
“…On the fourth attempt the policy development cycle from 2011-2012 was implemented and a carbon tax transitioning to an ETS was implemented from 2012-2014 only to be killed off following a general election and change of government in 2013 (see Freebairn, 2014;Wild et al 2015). Three further attempts have since been initiated; an Emissions Intensity Scheme in 2016 (see Simshauser & Tiernan, 2018), a Clean Energy Target in 2017 (see Finkel, 2017;) and a National Energy Guarantee from 2018 with this latter policy development cycle still on-foot with tentative bi-partisan support (see ESB, 2018).…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations
“…The appropriateness of an energy-only market design compared to alternative designs has been debated ever since the introduction of competitive energy markets (Cramton and Stoft, 2006;Cramton and Ockenfels, 2012;Hogan, 2005;Joskow, 2006;Schweppe et al, 1988). More recent studies have focussed on the additional complexities that intermittent and variable renewables bring to energy-only design, including the potential for further pricing volatility , interactions with environmental policies (Simshauser and Tiernan, 2018), and the risk of disorderly retirement of legacy dispatchable plant (Nelson, 2017). Joskow (2013) also concluded that revenue adequacy has emerged as a problem in many liberalized electricity markets.…”
Section: Introductionmentioning
confidence: 99%